Clinical characteristics and prognosis analysis of patients with myocardial infarction with non-obstructive coronary arteries in the Qinghai-Tibet plateau region - Zixu Fan; Zhiyu Wang; Yinghua Wang; Jianwei Ma; Mingyuan Niu; Min Zhang (Frontiers in Cardiovascular Medicine)
ObjectiveTo investigate the etiology and clinical characteristics of patients with myocardial infarction with nonobstructive coronary arteries (MINOCA) in the Qinghai-Tibet Plateau region.MethodsA retrospective analysis was conducted on 82 acute myocardial infarction (AMI) patients who underwent coronary angiography in the Department of Cardiology at Shigatse People's Hospital between December 2020 and December 2021. Patients were divided into two groups based on the results of coronary angiography: the myocardial infarction associated with obstructive coronary artery disease (MI-CAD group, n = 67) and the MINOCA group (n = 15). Etiology, medical history, laboratory findings, and in-hospital adverse events were analyzed for the MINOCA group.ResultsAmong the 15 MINOCA patients, the primary etiologies included: coronary plaque rupture in 2 cases (13.33%), coronary artery spasm in 2 cases (13.33%), coronary thrombosis or embolism in 1 case (6.67%), type 2 AMI in 1 case (6.67%), unrecognized myocarditis in 3 cases (20%), and other unknown causes in 6 cases. Compared with the MI-CAD group, MINOCA patients had a significantly lower BMI (p < 0.05). Laboratory findings revealed that LDL-C, apolipoprotein A, hs-cTnI, and CK-MB levels were significantly lower in the MINOCA group compared to the MI-CAD group (p < 0.01). Electrocardiogram results showed lower proportions of T-wave changes and ST-segment elevation in the MINOCA group than in the MI-CAD group (p < 0.05). Echocardiography findings indicated that MI-CAD patients were more prone to wall motion abnormalities (p < 0.001) and had significantly thicker interventricular septa compared to the MINOCA group (p < 0.05).ConclusionDue to factors such as hypoxic environments and different lifestyles, MINOCA in the plateau region exhibits characteristics distinct from those observed in low-altitude regions. Enhanced follow-up of these patients is recommended. Further exploration of the mechanisms underlying MINOCA in high-altitude environments is warranted to provide a basis for disease prevention and the development of individualized treatment strategies.